2023
DOI: 10.47391/jpma.7813
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic growth among frontline doctors fighting against COVID-19 at a tertiary care public hospital in Karachi, Pakistan

Abstract: Objective: To evaluate post-traumatic growth experienced by medical doctors who served coronavirus disease-2019 patients. Method: The cross-sectional study was conducted from December 1, 2021, to February 28, 2022, at the Civil Hospital, Karachi, and comprised medical doctors of either gender aged >22 years who directly provided care for at least one month to coronavirus disease-2019 patients. Other than demographic and professional profile of the subjects, data was collected using the Post-Traumatic Growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Furthermore, a strong level of group identity is indicative of lower levels of mental disorders. According to evidence in the field of clinical medicine, it has been found that various factors, such as social support, social inclusion, interventions aimed at improving social relationships, as well as tailored psychological interventions, have the potential to attenuate mental distress and facilitate post-traumatic growth in individuals who have undergone traumatic experiences, such as hospitalization due to Coronavirus ( 46 , 12 ). These outcomes substantiate the significance of perceived growth and the enhancement of positive mental changes among people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a strong level of group identity is indicative of lower levels of mental disorders. According to evidence in the field of clinical medicine, it has been found that various factors, such as social support, social inclusion, interventions aimed at improving social relationships, as well as tailored psychological interventions, have the potential to attenuate mental distress and facilitate post-traumatic growth in individuals who have undergone traumatic experiences, such as hospitalization due to Coronavirus ( 46 , 12 ). These outcomes substantiate the significance of perceived growth and the enhancement of positive mental changes among people.…”
Section: Discussionmentioning
confidence: 99%
“…Several aspects exert a substantial impact on an individual's posttraumatic growth, encompassing both intrinsic aspects as well as extrinsic aspects (9)(10)(11)(12). Furthermore, it is widely acknowledged that group identity has a pivotal part in influencing people's post-traumatic growth (13).…”
Section: Introductionmentioning
confidence: 99%